(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2026)
Caesarean section(CS) is most common surgical procedure done to protect mother and baby from untoward outcome of childbirth. Globally there is increasing trend of Caesarean section and a significant proportion is reported to be done on maternal request in absence of definite obstetric or medical indication. This is emerging as an issue of concern. The objectives were to explore the determinants of Caesarean section on maternal request, highlight potential risks and benefits of each mode of delivery and to formulate recommendations to optimize the rate of Caesarean section on maternal request. A literature review was conducted using Google scholar, Medline and Pubmed to identify factors that were relevant as an argument to meet the request for CS on maternal choice. Main determinants of CSMR are fear of pain during childbirth, uncertainty of fetal wellbeing in normal labour or chance of emergency CS during course of vaginal birth, previous negative experience of childbirth, perception of CS being safer and regarding CSRM as their right. Both mode of delivery has its own risk and benefits that has to be discussed with the women during pregnancy so that the women can have enough time to think and prepare herself. The attending health professional should be aware of his/her professional competence and duty and not influenced by any undue incentives or convenience. The basic ethical principles of autonomy, beneficence, non-malfiscence and justice are equally important for helping women decide the mode of delivery. Bangladesh J Obstet Gynaecol, 2025; Vol. 40(2): 115-121